2020
DOI: 10.48550/arxiv.2005.00072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Burning Questions on COVID-19: Did shutting down the economy help? Can we (partially) reopen the economy without risking the second wave?

Abstract: As we reach the apex of the COVID-19 pandemic across the globe, the most pressing question facing us all is: can we, even partially, reopen the economy without risking the second wave? Towards answering this question, we first need to understand if shutting down the economy helped. And second if it did, is it possible to achieve similar gains in the war against the pandemic while partially opening up the economy? To do so, it is critical to understand the effects of the various interventions that can be put in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…However, there is a tremendous amount of volatility in this form of COVID-19 data, and the fit of this prediction method may be improved with modeling structure or preprocessing of the donor pool. Agarwal et al [2020] proposed a model-free synthetic intervention method to predict unobserved potential outcomes after different interventions given a donor pool of observed outcomes with given interventions. They also provided useful guidelines for how to estimate the effects of potential interventions by giving recommendations for choosing the metric of interest, the intervention of interest, time horizons, and the donor pool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a tremendous amount of volatility in this form of COVID-19 data, and the fit of this prediction method may be improved with modeling structure or preprocessing of the donor pool. Agarwal et al [2020] proposed a model-free synthetic intervention method to predict unobserved potential outcomes after different interventions given a donor pool of observed outcomes with given interventions. They also provided useful guidelines for how to estimate the effects of potential interventions by giving recommendations for choosing the metric of interest, the intervention of interest, time horizons, and the donor pool.…”
Section: Discussionmentioning
confidence: 99%
“…They also provided useful guidelines for how to estimate the effects of potential interventions by giving recommendations for choosing the metric of interest, the intervention of interest, time horizons, and the donor pool. Although the methodology in Agarwal et al [2020] is quite general, there is no guarantee for theoretical properties in prediction without assuming any distributional structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second type of studies focused on policymaking, e.g., testing different mobility interventions to find optimal mobility reductions that balance the cost of viral spread with the economic cost associated with lockdowns, as well as implementing prediction models to advise policymakers. Several studies [ 13 , 14 , 15 , 16 ] sought to understand how the reduction in mobility affects the spread of COVID-19 cases across different POIs. In [ 13 ], researchers used Google mobility data and measured a correlation with the effective reproduction rate .…”
Section: Introductionmentioning
confidence: 99%
“…That study reveals that staying at home is effective at reducing , time spent at parks has little effect, while reducing mobility in other POIs has larger positive effects. In [ 15 , 16 ], researchers showed that mobility reduction of up to 40% in transit stations and retail and recreation venues decreased the number of cases and appeared to effectively “flatten the curve”. Furthermore, Refs.…”
Section: Introductionmentioning
confidence: 99%